Polymorphism of Sdr genes regulating seed dormancy in Triticum persicum Vav. and Triticum aethiopicum Jakubz. - M. S. Bazhenov; E. D. Guseva; V. S. Rubets (Вавиловский журнал генетики и селекции)
Preharvest sprouting of wheat grain, sporadically observed in many regions of cultivation of this crop, leads to deterioration of its food and sowing qualities. Seed dormancy is considered to be the main component of resistance to preharvest sprouting. This physiological state of seeds is regulated by many genes, and it depends heavily on environmental conditions. One of the regulators of seed dormancy in cereals is the Sdr4 gene (Seed dormancy 4), which was first studied in rice. In common wheat, the homologues of this gene (TaSdr-A1 and TaSdr-B1) are also involved in the regulation of seed dormancy. The search for valuable alleles in local varieties and endemic forms is a promising area of research aimed at increasing the resistance of crops to adverse environmental factors. In this study, Sdr genes were sequenced in several accessions of two tetraploid wheat species with limited cultivation areas: Persian wheat (Triticum persicum Vav.) and Ethiopian wheat (Triticum aethiopicum Jakubz.). As a result, the same Sdr-A1 and Sdr-B1 variants that had been found in common wheat were detected in these species. The Persian wheat accessions possessed only the Sdr-A1a allele, while Ethiopian ones, only Sdr-A1b. The analysis of F2 hybrids obtained from crossing these tetraploid species showed that the Sdr-A1b allele was associated with a lower germination index of grains than Sdr-A1a. This result was inconsistent with earlier association studies. Previously unknown polymorphisms were found in the promoter of the Sdr-B1 gene in the studied accessions. A deletion of 16 nucleotides was detected in the 3’-terminal region of the TraesCS2B02G215200 gene, located on the complementary DNA chain close to the 3’-end of the Sdr-B1 gene. Possible effects of the detected polymorphisms on the expression of Sdr genes are discussed.